Economic Growth Disparity among the Regions in Aceh, Indonesia - Azwar .; Abubakar Hamzah; Raja Masbar; Sofyan Syahnur (Aceh International Journal of Social Science, 2013)
Abstract - This study aims at investigating the extent of cumulative causation effect on economic growth disparity across the regions: Basajan-Pijay, Northeast, South-West, and Central-Inland in the Aceh Province, Indonesia. It also includes some others factors in determining economic growth disparity such as Gross Domestic Product (GDP) per capita, the concentration of economic activity areas, Human Development Index (HDI), the labour productivity of the region, the allocation of public investment as well as the accessibility among regions in the Aceh Province. To capture the goals of this study, it uses panel data during the period 2000 to 2010 consisting of 23 districts/cities of Aceh Province. The results show that the potential conditions for convergence because the dominant factor affecting the disparity without entering variable cumulative effect, the concentration of economic activity among regions have positive and negatively affected HDI. By entering variable cumulative effects, it turns HDI to have a negative effect, while the cumulative effect of the growth of inter-regional and the GDP per capita were positive. Thus, it can be said that the economic disparity among regions has the potential for convergence if and only if there is a policy intervention by the government in improving the quality of education, health, and consumer purchasing power to reduce the disparity. It is recommended that the Government of Aceh and District/City Government should encourage the growth of GDP per year, equal to or above the average growth of the national economy in order to increase labour productivity so that economic prosperity has also increased (spread effect is greater than backwash effect) because workings of the cumulative effect of growth within the region and among regions. Keywords : Disparity, Backwash effect, Spread Effect, Economic Growth, AcehPaper Type : Research Paper